The Differences Of Ijarah Financing and Conventional Lease On Islamic Law and Accounting Perspectives - Fitriani . (IQTISHADUNA, 2018)
The main objective of this study is to explore the nature of accounting for Ijarahfinancing and its differences with conventional lease financing from the Islamic law and accounting perspectives.The study makes a comparison between the International Accounting Standard on leasing (IAS 17); the accounting standard for Ijarah (FAS 8) as developed by the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI); and Statement of Financial Accounting Standards (Pernyataan Standar Akuntansi Keuangan/PSAK 107). The study found that there are major differences as to the nature of leasing and Ijarah, and as a result accounting principles that have driven all the three standards as well as accounting techniques developed for leasing and Ijarah are significantly different.